The Increasing of N, P, and K Nutrient in Palm Oil Under Prenursery Seedling By Application of Palm Oil Waste Compost and Endofitic Microbes - Hamidah Hanum; Lisnawati Lisnawati; Ahmad Rafiqi Tantawi (Syiah Kuala University, 2015)
Improvement of palm oil nutrient status since at the nursery is one of the efforts to improve plant resistance to Ganoderma attacks. Compost from palm oil waste and potentially endophytic microbes could potentially increase plant nutrients, especially N, P and K. This study aims to determine the potential of oil palm waste compost and endophytic microbes in increasing N, P and K in the plant oil palm under prenursery seedling. The study was conducted in a factorial experiment with the factors tested were types of compost, type and time of endophytic microbial inoculation. Research results indicating that the levels of N, P and K plants are not affected by the main factors and factor interactions of three factors. The concentration of of N, P, K soil is influenced by the interaction effect of two factors. The empty fruit bunch compost enriched every type endophyte showed better effects than compost midrib in increasing levels of P and K nutrient in plants and plant growth The application endofitic microbe after and before Ganoderma application inreased phosphor and potassium in plant and growth plant.